Recovery of the response function of a flexible membrane to a volume oscillation using double digital fringe projection technique and frequency filtering - Ubaldo Uribe López; Daniel Arturo Olivares Vera; David Asael Gutiérrez Hernández; Francisco Javier Casillas Rodríguez; José de Jesús Ibarra Sánchez (Nova Scientia, 2023)
This study presents a method to recover the response function of a flexible latex membrane undergoing a dynamic event by volume oscillation using Double Digital Fringe Projection to measure the profile of the surface in a sequence of frames. By applying a frequency filter to the interference pattern, a moiré pattern was obtained. Optical phase retrieval from individual frames was performed using the Isotropic Quadrature Transform Algorithm. This fringe projection technique enables full-field measurements, including edges where other techniques could not perform due to shadows generated by the tilt angle. The procedure was devised as a non-contact system to retrieve the deformation function of a flexible surface, enhancing a valuable aspect of the methodology. The results demonstrate successful recovery of the membrane response function, highlighting the relevance of the method for accurate deformation measurements using a straightforward system. These outcomes provide significant value for the development of precise measurement techniques for flexible structures in engineering applications, such as soft robotics, biomedical devices, and material science.